The market of reindeer meat in Finland, Scarce resource – high-valued products - Kaija Saarni; Jari Setälä; Leena Aikio; Jorma Kemppainen; Asmo Honkanen (Rangifer, 2007)
In 2004 the total production of reindeer meat was about 2.5 million kilos in Finland. About 1.8 million kilos were sold to consumers through the retailing or catering sector. The reindeer owners consumed themselves or sold directly to final customers about 0.7 million kilos of meat. The majority of reindeer meat processors were small enterprises. They employed less than five persons and the turnover was modest. Large companies processed most of the reindeer meat. These companies sold reindeer products like other products to nationwide retailing markets. Reindeer meat was sold most commonly as frozen meat. The main product was frozen sliced reindeer. The majority of the processed reindeer meat was sold to consumers through retailing. The export of reindeer meat was of minor importance to the processors. At the moment reindeer meat is a source of livelihood to a small and skilled group of professionals. Reindeer meat could be processed and sold more effectively to well paying niche markets by improving the cooperation between the companies. Poronlihatuotteiden markkinat Suomessa Abstract in Finnish / Tiivistelmä: Vuonna 2004 poronlihaa tuotettiin Suomessa noin 2,5 miljoonaa kiloa. Vähittäismyymälöiden, suurtalouksien, tukkuliikkeiden ja jalostusteollisuuden kautta myytiin kuluttajille noin 1,80 miljoonaa kiloa poronlihatuotteita. Poronomistajien omaan käyttöön mennyt tai poronomistajien suoraan kuluttajille myyty poronlihamäärä oli noin 0,7 miljoonaa kiloa. Lihanjalostajille poro on niukka raaka-aine, josta valmistetaan arvostettuja tuotteita erikoislihamarkkinoille. Yli puolet poronlihaa jalostavista yrityksistä on perustettu 1990-luvulla tai sen jälkeen. Näistä suurin osa on pieniä yrityksistä, joille poronlihanjalostus on tärkein toimiala. Pienten yritysten kilpailukyky perustuu lähialueelta hankittuun raaka-aineeseen ja ne ovat yleensä erikoistuneet lähimarkkinoihin, omaan tuotteistoon tai räätälöityyn asiakaspalveluun. Pääosa poronlihasta käsitellään kuitenkin muutamassa suuressa lihanjalostusyrityksessä, ...